Serum amyloid A and plasma fibrinogen concentrations in horses following emergency exploratory celiotomy. (12th May 2019) - De Cozar, M.; Sherlock, C.; Knowles, E.; Mair, T.
Summary: Background: Acute‐phase proteins may help assess the nature and severity of lesions and outcome in horses undergoing colic surgery. Objectives: To compare serum amyloid A and plasma fibrinogen concentrations ([SAA] and [fibrinogen]) in the immediate post‐operative period after exploratory celiotomy and determine their value in assessment of post‐operative complications and survival to discharge. Study design: Observational study. Methods: This study included horses over 1 year of age undergoing exploratory celiotomy. Surgical procedures, lesions, post‐operative care, complications and survival to discharge were recorded. [SAA] and [fibrinogen] were measured prior to surgery and 5 days post‐operatively. Statistical analyses included Yate's Chi‐square test, linear mixed effects model, Mann–Whitney U test and logistic regression. Results: Of 300 horses, 52.0% developed post‐operative complications and 83.7% survived to discharge, with significantly reduced chance of survival in horses that developed post‐operative complications (P<0.01). Median [SAA] at days 1, 2, 3, 4 and 5 and median [fibrinogen] at days 3, 4 and 5 were significantly different between horses that did and did not develop post‐operative complications (P<0.05). Median [SAA] at days 1, 4 and 5 were significantly different between horses that did and did not survive to discharge (P<0.05). Logistic regression revealed post‐operative complications to be associated with strangulating lesions (OR 2.35, 95% confidence interval [CI] 1.41–3.91, P≤0.001) and higher [fibrinogen] at admission (OR 1.21, 95% CI 1.00–1.45, P<0.05), and survival to discharge to be associated with lower [SAA] at 5 days post‐operatively (OR 0.965, 95% CI 0.94–0.99, P = 0.002). Main limitations: A large variety of lesions and complications prevented detailed analysis of associations between inflammatory markers, lesions and complications. Conclusions: Horses that develop post‐operative complications have acute‐phase responses of greater magnitudes and durations compared with those that do not develop complications. This is also seen in horses that do not survive to discharge. Measuring [SAA] daily and [fibrinogen] at admission, may help predict the development of post‐operative complications.